Association between Fecal Incontinence and Lower Urinary Tract Symptoms and their Impact on the Quality of Life of Patients with Prostate Cancer - Azevedo, Natália Burgos Freire; Abreu, Glícia Estevam de (Journal of Coloproctology, 2022)
Objective To evaluate the association of fecal incontinence (FI) and lower urinary tract symptoms (LUTS) in patients diagnosed with initial prostate cancer (PC) and after any therapeutic approach (surgery and radiotherapy).Methods Cross-sectional study using the Cleveland Clinic Incontinence Score (CCIS), the Fecal Incontinence Quality of Life (FIQL) questionnaire, and the International Consultation on Incontinence Questionnaire Overactive Bladder (ICIQ-OAB).Results A total of 84 patients with PC were included: 40 of them had not started treatment, 31 were submitted to radical prostatectomy (RP), and 13 were submitted to radiotherapy (RT). Those submitted to RT presented higher scores on the ICIQ-OAB (p = 0.01). When comparing the whole sample reagarding the patients with and without FI, we observed that the incontinents presented a higher frequency of urinary incontinence (UI) (p < 0.001). Moreover, when comparing patients with/without FI within their treatment groups regarding the presence of UI and FIQL scores, we identified that patients undergoing RP presented an association between UI and FI (p < 0.001) and a greater impact of FI on the FIQL (p < 0.001).Conclusion Patients submitted to RT present more intense LUTS. Moreover, patients with FI present a higher association with UI, and this association is more marked in those with FI submitted to RP.
Keywords: prostate cancer; radiotherapy; radical prostatectomy; urinary incontinence; fecal incontinence